Effect of Adapted Mindfulness Training in Participants With Elevated Office Blood Pressure: The MB‐BP Study: A Randomized Clinical Trial - Eric B. Loucks; Zev Schuman‐Olivier; Frances B. Saadeh; Matthew M. Scarpaci; William R. Nardi; Jeffrey A. Proulx; Roee Gutman; Jean King; Willoughby B. Britton; Ian M. Kronish (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Hypertension is a leading risk factor for cardiovascular disease. Despite availability of effective lifestyle and medication treatments, blood pressure (BP) is poorly controlled in the United States. Mindfulness training may offer a novel approach to improve BP control. The objective was to evaluate the effects of Mindfulness‐Based Blood Pressure Reduction (MB‐BP) versus enhanced usual care control on unattended office systolic BP. Methods and Results Methods included a parallel‐group phase 2 randomized clinical trial conducted from June 2017 to November 2020. Follow‐up time was 6 months. Outcome assessors and data analyst were blinded to group allocation. Participants had elevated unattended office BP (≥120/80 mm Hg). We randomized 201 participants to MB‐BP (n=101) or enhanced usual care control (n=100). MB‐BP is a mindfulness‐based program adapted for elevated BP. Loss‐to‐follow‐up was 17.4%. The primary outcome was change in unattended office systolic BP at 6 months. A total of 201 participants (58.7% women; 81.1% non‐Hispanic White race and ethnicity; mean age, 59.5 years) were randomized. Results showed that MB‐BP was associated with a 5.9‐mm Hg reduction (95% CI, −9.1 to −2.8 mm Hg) in systolic BP from baseline and outperformed the control group by 4.5 mm Hg at 6 months (95% CI, −9.0 to −0.1 mm Hg) in prespecified analyses. Plausible mechanisms with evidence to be impacted by MB‐BP versus control were sedentary activity (−350.8 sitting min/wk [95% CI, −636.5 to −65.1] sitting min/wk), Dietary Approaches to Stop Hypertension diet (0.32 score [95% CI, −0.04 to 0.67]), and mindfulness (7.3 score [95% CI, 3.0–11.6]). Conclusions A mindfulness‐based program adapted for individuals with elevated BP showed clinically relevant reductions in systolic BP compared with enhanced usual care. Mindfulness training may be a useful approach to improve BP. Registration URL: https://www.clinicaltrials.gov; Unique identifiers: NCT03256890 and NCT03859076.